2014
DOI: 10.1371/journal.pone.0079991
|View full text |Cite
|
Sign up to set email alerts
|

Sphagnum Mosses - Masters of Efficient N-Uptake while Avoiding Intoxication

Abstract: Peat forming Sphagnum mosses are able to prevent the dominance of vascular plants under ombrotrophic conditions by efficiently scavenging atmospherically deposited nitrogen (N). N-uptake kinetics of these mosses are therefore expected to play a key role in differential N availability, plant competition, and carbon sequestration in Sphagnum peatlands. The interacting effects of rain N concentration and exposure time on moss N-uptake rates are, however, poorly understood.We investigated the effects of N-concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 69 publications
2
66
0
Order By: Relevance
“…These high N uptake rates, especially for NH + 4 , from surface water or rainwater are indeed typical for Sphagnum spp. (Fritz et al, 2014). Simultaneously, the associated diazotrophs were still fixing N 2 at appreciable rates under these N-rich conditions, even though N 2 fixation is an energy demanding process (Vitousek et al, 2002).…”
Section: Diazotrophic Activity Under High N Conditionsmentioning
confidence: 95%
See 1 more Smart Citation
“…These high N uptake rates, especially for NH + 4 , from surface water or rainwater are indeed typical for Sphagnum spp. (Fritz et al, 2014). Simultaneously, the associated diazotrophs were still fixing N 2 at appreciable rates under these N-rich conditions, even though N 2 fixation is an energy demanding process (Vitousek et al, 2002).…”
Section: Diazotrophic Activity Under High N Conditionsmentioning
confidence: 95%
“…Peat mosses (Sphagnum spp.) function as a filter that very effectively absorbs particularly ammonium (NH + 4 ) but also nitrate (NO − 3 ) from atmospheric deposition, leading to N limitation in the rhizosphere of vascular plants (Lamers et al, 2000;Bragazza et al, 2004;Fritz et al, 2014). Since the availability of N determines primary production, there appears to be a close link between the N and C cycles (Hungate et al, 2003;Vitousek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…NH4 + is preferentially taken up by Sphagnum (Fritz et al, 2014;Liu et al, 330 2013; Wiedermann et al, 2009) because Sphagnum has a high cation exchange capacity 331 (Bates, 1992;Gunnarsson & Rydin, 2000). In addition, NH4 + has greater toxicity 332 (Gerendás et al, 1997;Krupa, 2003;Stevens et al, 2011).…”
Section: Science Of the Total Environment Chiwa Et Al Revised Msmentioning
confidence: 99%
“…(NH4 + ) versus oxidized (NO3 -) N on the N status of the Sphagnum moss and the (Manninen et al, 2011;Sheppard et al, 2014), possibly due to the greater toxicity of 97 NH4 + (Gerendás et al, 1997;Krupa, 2003;Stevens et al, 2011;Limpens and Berendse, 98 2003) coupled to preferential uptake of NH4 + by Sphagnum (Fritz et al, 2014;Liu et al, 99 2013; Wiedermann et al, 2009). For example, Manninen et al (2011) found that NH4 + 100 addition increased shoot N concentration of Sphagnum and decreased photosynthetic 101 variables (Fv/Fm) and shoot dry weight of Sphagnum.…”
mentioning
confidence: 99%
“…>10 kg N ha −1 year −1 ; Lamers et al 2000) on plants, since plants are assumed to be the main consumers of NH 4 + and NO 3 − in terrestrial ecosystems. Sphagnum mosses have been shown to be very efficient in retaining nitrogenous compounds from N deposition, preferentially taking up N in the form of NH 4 + (Fritz et al 2014). The effects of high N deposition on Sphagnum moss productivity are dependent on the level, where at low deposition levels, up to about 10 kg N ha −1 year −1 , mosses might still benefit from the additional N input (Lamers et al 2000;Berg et al 2012).…”
Section: Introductionmentioning
confidence: 99%